Environmental Triggers of Autoreactive Responses: Induction of Antiphospholipid Antibody Formation - Martirosyan, Anush; Aminov, Rustam; Manukyan, Gayane (Frontiers in Immunology, 2019)
Antiphospholipid antibodies (aPLs) comprise a diverse family of autoantibodies targeted against proteins with the affinity towards negatively charged phospholipids or protein-phospholipid complexes. Their clinical significance, including prothrombotic potential of anti-cardiolipin antibodies (aCLs), anti-β2-glycoprotein I antibodies (aβ2-GPIs) and lupus anti-coagulant (LA), is well-established. However, the ontogeny of these pathogenic aPLs remains less clear. While transient appearance of aPLs could be induced by various environmental factors, in genetically predisposed individuals these factors may eventually lead to the development of the antiphospholipid syndrome (APS). Since the first description of APS, it has been found that a wide variety of microbial and viral agents influence aPLs production and contribute to clinical manifestations of APS. Many theories attempted to explain the pathogenic potential of different environmental factors as well as a phenomenon termed molecular mimicry between β2-GPI molecule and infection-relevant structures. In this review, we summarize and critically assess the pathogenic and non-pathogenic formation of aPLs and its contribution to the development of APS.